2016
DOI: 10.5498/wjp.v6.i3.311
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-based magnetic resonance imaging investigation of poor and preserved clinical insight in people with schizophrenia

Abstract: AIMTo define regional grey-matter abnormalities in schizophrenia patients with poor insight (Insight-), relative to patients with preserved clinical insight (Insight+), and healthy controls.METHODSForty stable schizophrenia outpatients (20 Insight- and 20 Insight+) and 20 healthy controls underwent whole brain magnetic resonance imaging (MRI). Insight in all patients was assessed using the Birchwood Insight Scale (BIS; a self-report measure). The two patient groups were pre-selected to match on most clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 67 publications
1
16
1
1
Order By: Relevance
“…Structural neuroimaging studies have linked poor insight to reduced volume in several areas, including frontal 104,106,107 , temporal 107,108 , parietal 104,107 and occipital 107 regions, the thalamus 101 , basal ganglia 104 and cerebellum 107 , in both first-episode psychosis 109 and chronic schizophrenia 107 .…”
Section: Abnormalities In Brain Function As a Root Of Poor Insightmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural neuroimaging studies have linked poor insight to reduced volume in several areas, including frontal 104,106,107 , temporal 107,108 , parietal 104,107 and occipital 107 regions, the thalamus 101 , basal ganglia 104 and cerebellum 107 , in both first-episode psychosis 109 and chronic schizophrenia 107 .…”
Section: Abnormalities In Brain Function As a Root Of Poor Insightmentioning
confidence: 99%
“…Reduced cortical thickness has been observed in those with poorer insight in the superior temporal gyrus, parahippocampus and insula 107 as well as in the ventral lateral prefrontal cortex in schizophrenia, and in other frontal, parietal and temporal areas in first-episode psychosis 110 . Structural changes in white matter integrity, suggesting impaired connectivity, have also been found in chronic 111 and early phase psychosis 100,112 .…”
Section: Abnormalities In Brain Function As a Root Of Poor Insightmentioning
confidence: 99%
“…However, most of the studies addressing insight in non-affective psychosis compared patients in the chronic phase of schizophrenia with healthy volunteers, which might have introduced the effect of the illness as a confounding factor. For example, a recent study found that schizophrenia patients with poor insight had widespread reductions in GMV as compared to those with preserved insight [ 52 ] but this may have been confounded by long-term exposure to neuroleptic drugs[ 53 ]. In addition, many of the previous studies adopted a region of interest approach rather than the less constrained whole brain approach.…”
Section: Discussionmentioning
confidence: 99%
“…The role of medial temporal gyrus in insight deserves comment. Previous studies have shown reductions in this area in patients with poor insight[ 52 ] or have correlated its volume with insight in patients with schizophrenia[ 20 , 22 ]. This part of the temporal lobe has been classically associated with semantic and memory processing [ 58 ], and multimodal sensory integration [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…26 İç görüsüz şizofreni hastalarında yapılan görüntüleme çalışmaların-da, MSS'de yaygın nöronal dejenerasyon, sağ insulada kortikal incelme, temporal ve parietal gri madde hacminde azalma, frontotemporal beyaz cevher hacminde azalma, prefrontal, temporal ve serebellar nörodejenerasyonların olduğu bildirilmiştir. [26][27][28][29][30] İç görüsüzlüğün kliniğe olan olumsuz etkileri nedeniyle MSS düzeneklerinin anlaşılması önemlidir. 31 Bildiğimiz kadarı ile literatürde şizofreni hastalarında GHIP tabakasını inceleyen sadece bir çalışma varken, iç görüsüz şizofreni hastalarında retina kalınlığını inceleyen çalışma yoktur.…”
Section: Introductionunclassified